Analisis Kondisi Atmosfer Saat Kejadian Hujan Es (Studi Kasus: Kejadian Hujan Es Tanggal 29 November 2023 di Kabupaten Timor Tengah Selatan) - Maulidianto; Tempo, Neil Farel Rindra; Yosafat Donni Haryanto (Universitas Islam Negeri Alauddin Makassar, 2024)
Hail is an extreme weather phenomenon that rarely occurs in Indonesia. On November 26, 2023, there was heavy rain accompanied by hail in the Kapan area, South Central Timor Regency, East Nusa Tenggara at around 13:30 WITA. Further research on extreme events is needed to anticipate future extreme weather events. This study aims to analyze atmospheric conditions when hail occurs in the Kapan area on November 26, 2023. Research methods include analysis of field observation data, ECMWF ERA5 numerical modeling data, and Himawari-9 weather satellite image data. Based on observational data, hail occurs under unstable atmospheric conditions, such as a significant decrease in surface temperature, high humidity, and a significant decrease in atmospheric pressure before the event. Analysis of the vertical profile of the atmosphere based on model data showed that divergence, vertical velocity and relative humidity favored the formation of convective clouds. Satellite images showed that the temperature at the top of the cumulonimbus clouds during the ice storm was very low (-75.8°C). In addition, convective cloud cover (CCO) analysis confirmed the presence of cumulonimbus clouds covering the Kapan region during the hail period. All three methods can well describe the atmospheric conditions during hail events, these results are expected to provide insight into the atmospheric factors that contribute to the occurrence of hail in tropical regions such as Indonesia and can be used to better understand and mitigate the negative impacts of these extreme weather events.